2020
DOI: 10.47194/orics.v1i2.73
|View full text |Cite
|
Sign up to set email alerts
|

Student’s Worksheet Practically by Using Discovery Learning Model to the Ability of Understanding Concept and Mathematics Problem Solving at Grade VII Grade of SMPN 38 Padang

Abstract: The ability of understanding mathematical concept and problem-solving mathematics is one of aims of mathematic subject it is expected to develop in mathematics learning. Based on the observation that was doing by students of VII grade SMPN 38 Padang in 2019/2020 academic years, this research obtain that the students got difficulty in doing story problem that related in real life situation without illustration’s picture. It causes, mathematics learning still focused on text book and LKPD. LKPD that SMPN 38 Pada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…According to (Yulia et al, 2022), the deployment of such specialized teaching materials, including the implementation of PQ4R (Preview, Question, Read, Reflect, Recite, and Review) strategies within electronic LKPDs (E-LKPD), has been shown to significantly enrich the learning experience, rendering it more dynamic and interactive, thereby promoting students' engagement and cognitive development (Nirmala et al, 2021) Moreover, the ambit of scientific literacy transcends the confines of pure science to permeate diverse disciplines, including mathematics and social sciences, highlighting its interdisciplinary significance. The practicality and validity testing of LKPD through methodologies such as field trials and questionnaires have been instrumental in assessing its efficacy in bolstering students' comprehension, analytical capabilities, and problem-solving prowess (Suriani & Devita, 2020). Furthermore, the integration of LKPD based on Socio-Scientific Issues (SSI) has proven to be both valid and pragmatic, significantly enhancing the caliber of science education in junior high schools by fostering a more contextual and application-oriented learning environment (Putriana, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…According to (Yulia et al, 2022), the deployment of such specialized teaching materials, including the implementation of PQ4R (Preview, Question, Read, Reflect, Recite, and Review) strategies within electronic LKPDs (E-LKPD), has been shown to significantly enrich the learning experience, rendering it more dynamic and interactive, thereby promoting students' engagement and cognitive development (Nirmala et al, 2021) Moreover, the ambit of scientific literacy transcends the confines of pure science to permeate diverse disciplines, including mathematics and social sciences, highlighting its interdisciplinary significance. The practicality and validity testing of LKPD through methodologies such as field trials and questionnaires have been instrumental in assessing its efficacy in bolstering students' comprehension, analytical capabilities, and problem-solving prowess (Suriani & Devita, 2020). Furthermore, the integration of LKPD based on Socio-Scientific Issues (SSI) has proven to be both valid and pragmatic, significantly enhancing the caliber of science education in junior high schools by fostering a more contextual and application-oriented learning environment (Putriana, 2020).…”
Section: Introductionmentioning
confidence: 99%